Sistem kualitas dan standar penjaminan kualitas lembaga pendidikan - Khairi, Annisa Fhaudhila (Program Studi Magister Pendidikan Agama Islam, 2025)
This article reviews the quality system and standards for ensuring educational quality with the aim of providing a more comprehensive understanding of the mechanisms for evaluating and controlling quality in educational institutions. The educational quality system plays a role in regulating and assessing the implementation of education to ensure that the educational process and outcomes are in line with established standards. Quality assurance standards are used as a reference to ensure the achievement of quality and sustainable educational goals. The research method used is library research, which involves collecting and analyzing various relevant literature sources as the basis for discussion. This article is expected to serve as a scientific reference for researchers, educators, and educational institution managers in understanding the importance of quality systems and quality assurance in enhancing global competitiveness and educational quality. Abstrak Artikel ini mengulas sistem kualitas dan standar penjaminan mutu pendidikan dengan tujuan memberikan pemahaman yang lebih komprehensif mengenai mekanisme evaluasi dan pengendalian mutu di lembaga pendidikan. Sistem kualitas pendidikan berperan dalam mengatur dan menilai pelaksanaan pendidikan guna memastikan bahwa proses dan hasil pendidikan sesuai dengan standar yang telah ditetapkan. Standar penjaminan mutu digunakan sebagai acuan untuk menjamin pencapaian tujuan pendidikan yang berkualitas dan berkelanjutan. Metode penelitian yang digunakan adalah studi pustaka (library research), yaitu dengan mengumpulkan dan menganalisis berbagai sumber literatur yang relevan sebagai dasar pembahasan. Artikel ini diharapkan dapat menjadi referensi ilmiah bagi para peneliti, pendidik, dan pengelola lembaga pendidikan dalam memahami pentingnya sistem kualitas dan penjaminan mutu dalam meningkatkan daya saing dan kualitas pendidikan secara global.